Characteristics of Female Solo and Female Co-Offenders and Male Solo Sexual Offenders Against Children. (March 2019) - Williams, Rebecca; Gillespie, Steven M.; Elliott, Ian A.; Eldridge, Hilary J.
Studies have highlighted differences in the victim choice, offender, and offense characteristics of female and male sexual offenders. However, little is known about how solo and co-offending females differ from solo male sexual offenders. We compared the characteristics of 20 solo and 20 co-offending females (co-offended with a male and/or female accomplice), and 40 male sexual offenders against children. We found that solo female offenders showed the most evidence of personal problems, including depression and sexual dissatisfaction. Compared with male offenders, female co-offenders showed poorer self-management, but better sexual self-regulation. Male offenders had a greater history of offending and showed more evidence of sexual abuse supportive cognitions relative to both solo and co-offending females. These results are consistent with the need for a gender-specific approach to working with sexual offenders and may have implications for understanding the often complex treatment needs of these clients.